SIFAT MEKANIK DAN STRUKTUR MIKRO SAMBUNGAN LAS ALUMINIUM 6061 HASIL FRICTION WELDING - Hendry Wicaksana; Santoso Mulyadi; Ahmad Syuhri (ROTOR, 2016)
The study of the interface mechanical strength of metal alloy friction welded is essential for increasing of the quality of bonding between two materials. In the present study the material is 6061 aluminium alloy and the variation are friction time and chamfer angle. The purpose is to increase the mechanical strength of aluminium 6061 friction welded by combining friction time parameter and chamfer angle. The friction time variations were 60 and 120 second. Whereas the chamfer angles were 0o, 30o, 60o. The joined aluminium then tensile tested, hardness tested and also observed under microscope. The result of mechanical test shows that the variation 30o/120 second give the best result wich the Ultimate Tensile Strength as value as 15.86 N/mm2 and the brinell hardness as value as 92 BHN on Zud areas, 99 BHN on Zpd areas and 91 BHN on Zpl areas. Microstructure observation shows that there were porosity and crack on some testing spesimen.